The interplay of dietary sugar, chronic inflammation, and bladder cancer: mechanistic insights, evidence, and prevention strategies - Tratnjek, Larisa; Janev, Aleksandar; Kuret, Tadeja; Jerman, Urška Dragin (Frontiers in Immunology, 2026)
High dietary sugar intake has emerged as a key modulator of systemic inflammation and metabolic dysregulation, both of which are associated with an increased risk of several chronic diseases, including cancer. Although bladder cancer is primarily driven by factors such as smoking and occupational exposures, metabolic dysregulation may also play a contributory role. Experimental studies indicate that elevated glucose levels promote proliferation, epithelial-mesenchymal transition, increase invasion, and reduce autophagy in bladder cancer cells. Epidemiological evidence suggests associations of high dietary glycaemic index/load and high sugar consumption with bladder cancer risk, although findings for these dietary factors remain heterogeneous. Furthermore, epidemiological data consistently demonstrate a positive association between diabetes mellitus and increased bladder cancer incidence and adverse clinical outcomes. Mechanistically, hyperglycaemia and accumulation of advanced glycation end products (AGEs) can activate inflammatory signalling pathways, including NF-κB, MAPK, and the NLRP3 inflammasome, leading to increased cytokine production, immune dysregulation, and oxidative stress. High dietary sugar intake has also been shown to alter gut microbiota composition, typically reducing short-chain fatty acid (SCFA)-producing bacteria and promoting intestinal permeability, endotoxaemia, and sustained immune activation through TLR4-dependent pathways. Within the bladder tumour microenvironment, systemic inflammatory disturbances enhance oncogenic signalling cascades such as COX-2, JAK/STAT3, and NF-κB, thereby fostering epithelial-mesenchymal transition, angiogenesis, and potential resistance to therapy. Evidence suggests that maintaining well-regulated blood sugar levels may help lower the risk of bladder cancer. Adopting lifestyle habits such as whole-food, fibre-rich diets, probiotics, and regular physical activity supports metabolic and microbial homeostasis, SCFA-mediated immune regulation, and inflammation reduction, thereby serving as a preventive strategy. This review aims to synthesise current evidence on the complex interplay between dietary sugar intake, gut microbiota dysregulation, systemic inflammation, and bladder cancer, and to highlight potential preventive dietary interventions.